Exploring elite athlete experiences of growth: impact of the COVID-19 pandemic on well-being - Howard-Cook, E.; Howells, K. (The Sport Psychologist, 2024)
The aim of the current study was to explore elite athletes` experiences of the COVID-19 pandemic and its impact on both growth and well-being. Informed by two complementary theoretical models, this research focused on elite athletes` potential to experience growth. Five elite athletes completed the Stress-Related Growth Scale-Revised and underwent semistructured interviews to develop a narrative of their experiences. Through a thematic analysis, we articulated elite athletes` experiences of both illusory and real adversarial growth following the COVID-19 pandemic. Four themes illustrated their experiences: the COVID-19 experience, searching for positives, self-transformation, and the social impact. A fifth theme, well-being, was integral throughout, involving the continued protection and development of athlete well-being. Future research recommendations and implications include further exploration of adversarial growth experiences after the pandemic and long-term effects of the pandemic on elite athletes, the creation of an adversarial growth measure, and engagement with this research to inform support measures to decrease the impact of adversity on elite athletes` well-being.